ANIMASI EDUKASI MENGENAL TAJWID & HURUF HIJAIYAH UNTUK SISWA KELAS 4 SEKOLAH DASAR - Dian Gustina; Sulistianto SW; Fajar Raditya (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2014)
Comprehension in reading the Qur'an for Muslims in Indonesia is something that must be controlled. This is reflected from the target as a child before the child is of school age, the parents are directly or indirectly teach things that should be done as part of the implementation in running his religious beliefs. In fact most of elementary school-age children are still many who do not understand in reading the Qur'an recitation and readings mainly due to the lack of guidance hijaiyah both at home and at school. In order to facilitate primary school age children in recognizing Tajweed & hijaiyah, especially grade 4 elementary school children designed the animation education and letters Hijaiyah familiar recitation by default by using Multimedia. With this educational animation creation is expected to be deepened again what tools are needed in Model Learning Tajweed and Letters Hijaiyah, in addition to the existing teaching methods for this.